The 4 Noble Truths: The natural law regarding the nature of the truth of life and the path to liberation - Phramahaveera Veeranago (Singto) (Journal of Contemporary Buddhist Society = JCBS, 2022)
This article is about the subject. Orderliness of nature; the five aspects of natural law; 1) Physical inorganic order: physical laws, 2) Physical organic order, biological laws, Psychic law. 4) Order of act and result; the law of Kamma; moral laws and 5) Order of the norm; the general law of cause and effect; causality and conditionality. The Noble Truth is the noblest truth. The truth that makes people noble The truth of the Noble Lord and the truth The Noble Truths are a process of reaching the truth from the point of view of Buddhist philosophy. It has four values: 1) It is a method of wisdom. 2) It is a method of solving problems and managing one's life with one's own wisdom. 3) It is a truth related to one's life. everyone Regardless of whether humans wander off into the matter. 4) It is a central principle of truth. Therefore, the Noble Truth The four noble truths are suffering the cause of suffering, the cessation of suffering, and the path for the cessation of suffering. The Buddha praised and advised Buddhists to study seriously. Because knowing the Noble Truths can lead to the cessation of defilements and suffering.